Penerapan Terapi Bermain Pada Anak Usia Prasekolah Uuntuk Menurunkan Kecemasan Akibat Hospitalisasi di Charitas Hospital Palembang - Lusia Garsiana Yunita; Maria Tarisia Rini; Ketut Suryani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Preschool children have weak immunity, which causes children to get sick easily and receive hospital treatment which causes anxiety due to hospitalization. Anxiety results in fear of new environments, frequent crying, being spoiled, aggressive, depression and even causing trauma. Playing at preschool age is an important activity, playing by matching pictures can influence a person's feelings by stimulating the nervous system in the brain to regulate emotions. This research uses a descriptive case study. The research subjects were three people, the data collection instrument was carried out using the FIS (Faces Image Scale) scale observation sheet. After being given play therapy, the results were obtained on the first day at F before being given the intervention, the anxiety scale was 4, after being given the intervention, the anxiety scale was 4, A anxiety before 5 and after 4, S anxiety before 4 and after 4. On the second day, F anxiety before 4 and after 3, A anxiety before 4 and after 3, S anxiety before 4 and after 3. The third day F anxiety before 3 and after 2, A anxiety before 3 and after 2, S anxiety before 3 and after 2. After intervention for 3 consecutive days, it can be concluded that providing picture-matching play therapy to preschool children can reduce hospitalization anxiety. Parents should continue to meet children's play needs by inviting children to play and facilitating games according to what the child likes, and nurses are expected to focus on modifying children's play.